Molecular control of Schwann cell migration along peripheral axons: Keep moving! - Heermann, Stephan (Landes Bioscience, 2013)
The development of the peripheral nervous system (PNS) is a highly dynamic process, during which motor and sensory axons innervate distal targets, such as skeletal muscles and skin. Axonal function depends critically on support from Schwann cells, the main glial cell type in the PNS. Schwann cells originate from the neural crest, migrate along outgrowing axons and associate with axons along their entire length prior to ensheathment or myelination. How axonal growth and the migration of Schwann cells is coordinated at the level of reciprocal axon-glial signaling is the fascinating subject of ongoing research. Neuregulin-1 (NRG1) type III, an axonal membrane-bound ligand for receptor tyrosine kinases of the ErbB family, acts as a “master regulator” of peripheral myelination. In addition, NRG1-ErbB signaling directs the development of the Schwann cell lineage and regulates the proliferation and survival of Schwann cells. Studies in zebrafish have identified a direct role of NRG1 type III in Schwann cell migration, but to what extend NRG1 serves a similar function in the mammalian PNS is not clear. We have employed a mouse superior cervical ganglion explant culture system, in which the migration of endogenous Schwann cells along outgrowing axons can be visualized by time-lapse imaging. Using this approach, we found that NRG1 type III-ErbB signaling regulates the colonization of distal axonal segments by Schwann cells. However, our data suggest an indirect effect of NRG1 type III-ErbB signaling via the support of Schwann cell survival in proximal axonal regions rather than a direct effect on Schwann cell motility.